GENDER STEREOTYPES BY PRESENTING A FEMALE PROTAGONIST PORTRAYED IN THE "NEIL'S BURGER DIVERGENT (2014)" MOVIE - Maheswara, Rahayasa; Prastiwi, Yeni (English Review: Journal of English Education, 2023)
This study aims to show a positive representation of feminism in Divergent films and find the implied meaning behind the presentation of feminism. this study uses a critical approach, qualitative methodology, and social research methods, in particular Roland Barthes' model of semiotics. Roland Barthe's athletic session model uses the concept of denotation and connotation as key analysis. This search analysis is done by focusing only on the main elements of narrative in films, especially space and time, characters, conflicts, and goals. The results of this research show that the two rhymes of representation of feminism in Divergent films and the notion that women are sexy, weak, and tend to act out their emotions than logic, it is not true. Social values and women's way of life appear in this rumor which is done by the main character named Tris. In a conclusion, the representation of feminism can be displayed through the main narrative elements in the film, such as space and time, characters, conflict, and goals. And also, this research gives findings about pacifism (K). There is 3 denotation, 2 connotations, and 1 myth in divergent film.